2009
DOI: 10.3354/cr00816
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, aridity thresholds, and population growth dynamics in China over the last millennium

Abstract: ABSTRACT:The relationship between climate and population has long been discussed, but rarely has it been quantitatively measured. Hence, the relationship remains ambiguous. In the present study, we employ fine-grained temperature, aridity threshold, and population data, together with logistic models and spatial statistics, to quantitatively explore how far climate change affected population growth dynamics in China from 1000 to 1979. Statistical results confirm that cold climate was associated with below avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…Using logistic models and spatial statistics, we systematically demonstrated that long-term cooling significantly shrank the carrying capacity of agrarian China, resulting in below average population growth and southward shifts of the population, and that the reverse scenario was also true. Our preliminary results provided strong evidence for the climate-population relationship in historical China, and demonstrated that temperature was more influential than aridity threshold in explaining fluctuations in population size and shifts in population distribution (Lee et al 2008(Lee et al , 2009). In the present study, we further explore the climate-population relationship via an empirical approach.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Using logistic models and spatial statistics, we systematically demonstrated that long-term cooling significantly shrank the carrying capacity of agrarian China, resulting in below average population growth and southward shifts of the population, and that the reverse scenario was also true. Our preliminary results provided strong evidence for the climate-population relationship in historical China, and demonstrated that temperature was more influential than aridity threshold in explaining fluctuations in population size and shifts in population distribution (Lee et al 2008(Lee et al , 2009). In the present study, we further explore the climate-population relationship via an empirical approach.…”
Section: Introductionmentioning
confidence: 58%
“…To address this controversy, we quantitatively verified the climate-population relationship described in qualitative studies (Lee et al 2008(Lee et al , 2009). Using logistic models and spatial statistics, we systematically demonstrated that long-term cooling significantly shrank the carrying capacity of agrarian China, resulting in below average population growth and southward shifts of the population, and that the reverse scenario was also true.…”
Section: Introductionmentioning
confidence: 93%
“…More recent breakthroughs came from research adopting quantitative approaches to all known cases of social crisis. These studies show that, in recent history, climate change was responsible for the outbreak of war, dynastic transition, and population decline in China, Europe, and around the world because of climate-induced shrinkage of agricultural production (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, the underlying causal linkages from climate change to agricultural production and various human catastrophes in history have not been addressed scientifically.…”
mentioning
confidence: 99%
“…Several studies have SD standard deviation, CV coefficient of variation * indicates significance for the Mean-comparison test in relative to the Mean 3.07 of the whole period, * P \ 0.10; ** P \ 0.05; *** P \ 0.01 demonstrated that the effects of short-term and long-term changes in different climatic elements on different social factors are highly variable. Long-term temperature changes are typically considered as being much more influential than short-term changes in temperature, aridity threshold or precipitation for explaining fluctuations in population size and shifts in the population distribution (Lee et al 2009), macro-economic cycles in Europe (Pei et al 2014) and large-scale human socioeconomic crises (Zhang et al 2011). Short-term climate variations merely raised prices, while longer climate changes resulted in economic crises (Pei et al 2013).…”
Section: Short-and Long-term Effects Of Climate Change On Macro-economentioning
confidence: 99%
“…For a heavily agrarian-based society in historical China, this mechanism is also the most direct and primary pathway through which past climate changes affected the rise and fall of macro-economic development. Long cool periods shorten the length of the growing seasons and reduce the elevation and latitude at which crops can be grown, which decreases the amount of land available for cultivation and leads to either a decline in total output or more intensive cultivation with lower yields, particularly in higher latitude regions (Galloway 1986;Lee et al 2009). Higher ratios for poor harvests were found during the cold periods Yin et al 2014).…”
Section: Potential Mechanism For Climatic Effectsmentioning
confidence: 99%